2021
DOI: 10.3390/molecules26040903
|View full text |Cite
|
Sign up to set email alerts
|

Hovenia dulcis Thumberg: Phytochemistry, Pharmacology, Toxicology and Regulatory Framework for Its Use in the European Union

Abstract: Hovenia dulcis Thunberg is an herbal plant, belonging to the Rhamnaceae family, widespread in west Asia, USA, Australia and New Zealand, but still almost unknown in Western countries. H. dulcis has been described to possess several pharmacological properties, such as antidiabetic, anticancer, antioxidant, anti-inflammatory and hepatoprotective, especially in the hangover treatment, validating its use as an herbal remedy in the Chinese Traditional Medicine. These biological properties are related to a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 79 publications
0
25
0
Order By: Relevance
“…Given the huge medical costs, it is urgent to find effective therapeutic strategies to prevent and treat vascular calcification. DMY, as the most abundant natural flavonoid in vine tea, can also be found in traditional medical plants including Hovenia dulcis and Cedrus deodara and plant-based fruits including grapes and red bayberry [33][34][35]. Several studies showed that DMY had multiple cardiovascular protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Given the huge medical costs, it is urgent to find effective therapeutic strategies to prevent and treat vascular calcification. DMY, as the most abundant natural flavonoid in vine tea, can also be found in traditional medical plants including Hovenia dulcis and Cedrus deodara and plant-based fruits including grapes and red bayberry [33][34][35]. Several studies showed that DMY had multiple cardiovascular protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Hovenia dulcis (H. dulcis) Thunb, also named as Japanese raisin tree, distributed in China, Japan, Korea, as well as other parts of world, presents another natural resource of DMY [8][9][10], along with Cedrus deodara (Roxb. ex D.Don) G.Don, Pinaceae, a large evergreen coniferous tree that grows on the slopes of western Himalayas in Eastern Afghanistan, Northern Pakistan, India and southwestern Tibet, China.…”
Section: Natural Resources Of Dmymentioning
confidence: 99%
“…In another study, after DMY was orally administered to rats at a dose of 100 mg/kg, the samples of urine, feces, and plasma were collected and the metabolites of DMY were determined based on MS 2 data of UPLC-QTOF-MS. In urine and feces, 8 metabolites of DMY were identified and their transformations were predicted to belong to glucuronidation (9), dehydroxylation (3, 4), reduction (2), methylation (7, 8), or sulfation (10), as well as both dehydroxylation and reduction reactions (11). However, metabolites of DMY were not detected in plasma [66].…”
Section: Metabolites Of Dmy In Urine Feces and Plasmamentioning
confidence: 99%
“…Generally, H. dulcis has a long history been used as a traditional Chinese herb for the treatment of liver disease and alcohol poisoning [1,2]. Recently, a numerous number of in vitro and in vivo studies have demonstrated that H. dulcis possesses diverse health-promoting effects, such as anti-diabetic, anti-cancer, anti-oxidant, antiinflammatory, and hepatoprotective effects [3,4]. Usually, these health-promoting effects are correlated to different bioactive ingredients that exist in H. dulcis, such as polyphenolicprotein-polysaccharide ternary complexes, polysaccharides, polyphenolics, flavonoids, and saponins [1][2][3][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a numerous number of in vitro and in vivo studies have demonstrated that H. dulcis possesses diverse health-promoting effects, such as anti-diabetic, anti-cancer, anti-oxidant, antiinflammatory, and hepatoprotective effects [3,4]. Usually, these health-promoting effects are correlated to different bioactive ingredients that exist in H. dulcis, such as polyphenolicprotein-polysaccharide ternary complexes, polysaccharides, polyphenolics, flavonoids, and saponins [1][2][3][5][6][7]. Especially, polyphenolic-protein-polysaccharide ternary complexes obtained from H. dulcis also possess diverse bioactivities, including anti-oxidant, antiglycation, and anti-diabetic effects [2,5].…”
Section: Introductionmentioning
confidence: 99%